Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1128/jb.185.23.6883-6892.2003
|View full text |Cite
|
Sign up to set email alerts
|

Quinolone Resistance Due to Reduced Target Enzyme Expression

Abstract: We report for the first time low-level quinolone resistance mediated by decreased expression of topoisomerase IV in Staphylococcus aureus. A single-step mutant of wild-type S. aureus strain ISP794, P18 selected by using twice the MIC of premafloxacin, had four-and four-to eightfold greater MICs of premafloxacin and ciprofloxacin, respectively, than the wild type. Sequencing of parEC and gyrBA with their promoter regions revealed a point mutation (G3A) 13 bp upstream of the start codon of parE. Genetic linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 55 publications
(59 reference statements)
2
44
1
Order By: Relevance
“…In support of this notion, S. aureus mutants overexpressing penicillin-binding protein 4, one of the drug targets of ␤-lactams, leads to elevated ␤-lactam resistance expression (12,16). On the other hand, Ince and Hooper (19) reported that decreased transcription of the parEC operon in first-step fluoroquinolone-resistant mutants of S. aureus led to increased resistance to fluoroquinolones, making our findings somewhat contradictory. Furthermore, in contrast to our findings, growth in the presence of salicylate actually reduces fusA transcription in E. coli and M. tuberculosis (8,40).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…In support of this notion, S. aureus mutants overexpressing penicillin-binding protein 4, one of the drug targets of ␤-lactams, leads to elevated ␤-lactam resistance expression (12,16). On the other hand, Ince and Hooper (19) reported that decreased transcription of the parEC operon in first-step fluoroquinolone-resistant mutants of S. aureus led to increased resistance to fluoroquinolones, making our findings somewhat contradictory. Furthermore, in contrast to our findings, growth in the presence of salicylate actually reduces fusA transcription in E. coli and M. tuberculosis (8,40).…”
Section: Resultscontrasting
confidence: 72%
“…Both parE and fusA were identified as salicylate inducible via SCOTS analysis, and this was confirmed by real-time PCR (Table 2). Even though parE and parC are carried on a polycistronic transcript (19), neither was upregulated on the array. fusA was also upregulated by salicylate on the array analysis, but this proved insignificant.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, as has been previously demonstrated with the isogenic strains SS1 and 1734-J-AE-15, bearing the Ser84Leu and the Gly82Asp mutations in GyrA, respectively, the MIC of ciprofloxacin was similar to or only twofold higher than that of the wild type (30). Therefore, to account for the additional resistance phenotype of these mutants, we sequenced the entirety of the gyrA, gyrB, parC, and parE genes as well as the promoter region of parE or gyrB, the former of which has been recently described as a quinolone resistance mechanism through reduced enzyme expression (16). We found only a novel deletion of amino acids Arg, Gln, and Glu at positions 215 to 217 of ParE in DX-619-E but no additional mutation in DX-619-C.…”
Section: Characterization Of Dx-619-selected Single-step Mutantsmentioning
confidence: 99%
“…Fluoroquinolones vary in their antibacterial activity by preferentially targeting DNA gyrase, DNA topoisomerase IV, or both. Bacterial resistance to fluoroquinolone activity may also occur through alteration in quinolone targets, decreased uptake of the drugs, expression of efflux pump systems, and mobile elements which may confer resistance (Ince andHooper 2003, Ruiz 2003).…”
Section: Discussionmentioning
confidence: 99%